Effect of hydrocolloids on gluten proteins, dough, and flour products: A review. (February 2023) - Zhang, Huijuan; Liu, Shuchang; Feng, Xuejia; Ren, Feiyue; Wang, Jing
Graphical abstract: Highlights: Anionic and nonionic hydrocolloids are connected with gluten protein by electrostatic interactions and hydrogen bonds, respectively. Hydrocolloids mainly affect the characteristics of gluten proteins through the action on the gluten network and secondary structures. The characteristics of gluten proteins, dough and flour products are the primary evaluation criteria. Abstract: Hydrocolloids are among the most common components in the food industry, which are used for thickening, gel formation, emulsification, and stabilization. Previous studies have also found that hydrocolloids can affect the structures and properties of gluten proteins, dough, and flour products. In this review, hydrocolloids were separated into three categories: anionic, nonionic, and other hydrocolloids, and reviewed the effects of common hydrocolloids on gluten proteins, dough, and flour products. Hydrocolloids can affect the structures and properties of gluten proteins through gluten-hydrocolloids interaction, secondary structures, disulfide bonds, environment of aromatic amino acids, and chemical bonds. The properties of dough are affected by rheological, fermentation, and thermomechanical properties. Hydrocolloids are widely used in bread, Chinese steamed bread, noodles, yellow layer cake, and so on, which mainly affect their appearance, texture, and aging speed. This comprehensive review provides a scientific guide for the development and utilization of hydrocolloids and their applications in flour products, and provides a theoretical basis for improving the processing characteristics of products.